2013
DOI: 10.1177/0194599813509779
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Parathyroid Function Using Carbon Nanoparticles during Thyroid Surgery

Abstract: Our randomized study revealed that CN suspension injection was feasible and appeared to be beneficial for patients undergoing thyroid surgery because the incidence of symptomatic hypocalcemia was lower compared with controls. Therefore, this technology and technique should be more widely considered for thyroid cancer therapy. Additional studies with more patients and longer follow-up times will be needed for a thorough evaluation of this methodology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 18 publications
2
51
1
Order By: Relevance
“…Some previous studies have demonstrated that CNs are beneficial for visualizing the lymph nodes and for distinguishing and preserving the parathyroid glands. On the contrary, other studies found no advantage of CNs 18,24. In addition, some indexes, such as postoperative hypocalcemia, are easily influenced by confounding factors such as the postoperative therapeutic selection, calcium supplements, and individual differences.…”
Section: Resultsmentioning
confidence: 93%
“…Some previous studies have demonstrated that CNs are beneficial for visualizing the lymph nodes and for distinguishing and preserving the parathyroid glands. On the contrary, other studies found no advantage of CNs 18,24. In addition, some indexes, such as postoperative hypocalcemia, are easily influenced by confounding factors such as the postoperative therapeutic selection, calcium supplements, and individual differences.…”
Section: Resultsmentioning
confidence: 93%
“…In consideration of the ideal effects and low side effects, carbon nanoparticles have been used in different kinds of cancer operations, like breast cancer [18], thyroid cancer [19], and colorectal cancer [11]. At present, carbon nanoparticles have been used more widely in China [18, 19, 34].…”
Section: Discussionmentioning
confidence: 99%
“…At present, carbon nanoparticles have been used more widely in China [18, 19, 34]. In our study, we localized colorectal cancer and traced lymph nodes with carbon nanoparticle suspension to evaluate their effectiveness in laparoscopic colorectal resection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations